An anxious inheritance: religious others and the shaping of Sunnī orthodoxy - Hughes, Aaron W. (Oxford University Press, 2022)
"This study is about the tensions between the early framers of Islam and non-Muslims in the early Islamic period. More specifically, it is about how these early framers struggled with religious others, both external and internal, and how this struggle was ultimately responsible for the creation of what would emerge as (Sunnī) orthodoxy. While the latter would appear as the natural outgrowth of Muhammad's preaching to those doing the framing, it was ultimately little more than a subsequent development accompanied by a retroactive projection onto the earliest period. Non-Muslims (among them Christians, Jews, Zoroastrians) and the "wrong" kinds of Muslims (e.g., Shīʻa) became integral-by virtue of their perceived stubbornness, infidelity, heresy, or the like-to understand what true religion was not and, just as importantly, what it should be. Without such religious others proper belief could not be articulated and orthodoxy would simply have remained adrift in its own inchoateness"--